"Anchoring" the World University Rankings - Bowman, Nicholas; Bastedo, Michael (International Higher Education, 2011)
Reputation scores are a key problem with international rankings. Our study shows that the initial Times Higher Education rankings had a disproportionate impact on people's assessment of international university reputations.